ANTARA ISLAM DAN BARAT : PANDANGAN MOHAMMED ARKOUN MENGENAI KEMODERNAN - Tambunan, Sihol Farida (Jurnal Masyarakat dan Budaya, 2003)
Mohammed Arkoun is an Algerian thinker who was educated at the University of Sorbonne, French and acquired French citizenship. He combined Western methodology to interprete the Islamic Script. In politics, he was against the concept of the Islamic state because its undemocratic character. He proposed the Islamic thinkers not to be afraid of modernity that comes from the Western world. He even suggested the Islamic thinkers to interprete Al Qur’an by using the modern sociology method that comes from the West instead of traditional methods. So, that modern method would enrich the interpretation.